Alpha-sulfo-higher fatty acid-lower alcohol ester- and amide-based detergent laundry bars and process for manufacture thereof - BARONE; PATRIZIA; RAMACHANDRAN; PALLASSANA N (1987)
Detergent laundry bars which are mild to the hands of a user, of good foaming properties during hand washing of laundry and of good processing characteristics, include 10 to 30% of water soluble salt of alpha-sulfo-higher fatty acid-lower alcohol ester, 10 to 50% of builder for such detergent, a bodying proportion, in the range of 20 to 70%, of water insoluble powder and/or sodium sulfate filler, and 5 to 20% of water. Preferably, this improved detergent laundry bar includes 18 to 22% of sodium alpha-sulfo-higher fatty acid methyl ester, 8 to 20% of sodium tripolyphosphate, 5 to 15% of sodium carbonate, 2 to 5% of sodium silicate, 20 to 35% of calcium carbonate, 5 to 15% of talc and 10 to 15% of water. Also within the invention is a process for manufacturing such detergent laundry bars wherein the components of the laundry bar composition which are in powder form are all pre-mixed, followed by admixing, with the pre-mix, of liquid components of the detergent composition, including sodium silicate, in aqueous solution, water and perfume, in that order, and the mixture is amalgamated, milled, plodded under vaccum, cut to desired lengths and pressed to desired form.